[Commentary on] Haas, Jere D. and Thomas Browlie IV. 2001. Evidence that iron deficiency anemia causes reduced work capacity - Horton, Susan; Levin, Carol E. (2001)
This commentary assesses the strength of the causal evidence presented by Haas and Brownlie in this supplement and examines the potential magnitude of iron-deficiency anemia on welfare. From both the laboratory and field experiments, the evidence is strong and suggests that the potential magnitude of the effect of iron-deficiency anemia on work productivity is substantial. This commentary briefly discusses some of the limitations of using the estimates of effects on physiological capacity for measuring the effect on the social and economic well-being of individuals and society. Biological data are relevant to social and economic development, but additional field studies may be as important as the laboratory experiments to answer questions that also affect work productivity, household maintenance and child raising activities, and hence affect social and economic development. We extend the critical evidence review of human field studies that received disproportionately less attention than the laboratory studies in Haas and Brownlie. We provide some estimates of the magnitude of effects on well-being based on how this information has been used. Future field studies that examine the effect of iron-deficiency anemia and work output in an economic sense should measure increases in productivity but should complement this information with data on wages, income or some measure of profits to derive a money metric measure of increased productivity. Additional information on individual time allocation in household work, child care and leisure may also be required to capture social benefits deriving from improved work capacity. -- Authors' Abstract